On The Tribological Performance Of Modified Industrial Rubber (DPNR And Polyisoprene) - Md. Nasir, Ramdziah (2009)
This study describes how this techniques can be used to highlight the differences in the carbon black loading, blending compound in influencing the tribological behavior and also to show these effect can be used to predict wearing and friction distribution on rubber surface on a more quantitative level. The main objective of this work is to develop and modify industrial rubber, i.e. deproteinised natural rubber (DPNR) and synthetic polyisoprene (PIR). Secondly, to understand the physical, mechanical and tribological properties of these materials as influenced by the addition of soft and hard carbon black (CB), specifically the role of C-black in improving the friction and wear characteristics.